Large scale atmospheric conditions favoring storm surges in the North and Baltic Seas and possible future changes - Schade, Nils H.; Jensen, Corinna; Kruschke, Tim (Frontiers in Environmental Science, 2025)
Climate change will not only cause significant sea level rise but is likely to also change the large-scale atmospheric circulation. Here, we analyse atmospheric conditions that caused storm surges at the German North and Baltic Sea coasts. Possible future changes thereof are examined using a multi-model CMIP6 ensemble of global climate simulations under different emission scenarios. Observed storm surges are analyzed from peak water level observations at the gauge stations Koserow, Warnemünde, Kiel-Holtenau, and Flensburg along the German Baltic Sea coast, and at Cuxhaven located in the North Sea. For the classification of the meteorological conditions on the respective day of a storm surge we use two atmospheric reanalyses. We employ a simple weather type classification approach, based on daily mean sea-level pressure fields as input. This approach can be applied easily to global or regional climate model simulations which makes it an effective tool for climate change investigations. For each of the gauge stations, a proxy for storm surge favorable atmospheric conditions–the effective wind–is derived. Westerly and cyclonic weather types are the atmospheric drivers of observed storm surges at Cuxhaven. The most favorable weather types at the stations Koserow and Warnemünde are north-east and cyclonic, adding anticyclonic for Kiel-Holtenau and Flensburg. Towards the end of the 21st century, the CMIP6 ensemble projects a significant increase in the frequency of westerly effective winds for Cuxhaven under the scenarios SSP3-7.0 and SSP5-8.5. In contrast, a significant decrease of easterly effective winds is projected for all four locations at the Baltic Sea coast. These findings are a result of the tendency towards strengthened westerly stream and a north-western shift of the storm tracks in climate projections over these regions that is also described by other investigations. Our results indicate that the increasing risk for extreme water levels associated with the virtually certain sea-level rise is additionally fueled by more frequent weather patterns favoring storm surges at the German North Sea coast, while changes of the large-scale circulation may dampen the increase of storm surge risk associated with sea-level rise at the German Baltic Sea coast to some degree.